Dosimetric Study of Voluntary Deep Inspiratory Breath-Hold (V-DIBH) Vs Free Breathing (FB) Technique on Organ Doses for Left-Sided Breast Cancer - Deepti Sharma; Nidhi Marjara; Vineeta Goel; Nithya Loganathan (Iranian Journal of Medical Physics, 2022)
Introduction: Long term cardiac morbidity is a concern with left sided breast/chest wall irradiation. In this present study, we have evaluated the Impact of Voluntary deep inspiratory breath hold (V-DIBH) Vs Free Breathing (FB) technique on heart and lung doses for left-sided breast cancer with audio visual guidance. Material and Methods: A total of 31 patients diagnosed with left breast cancer were found to be suitable for V-DIBH. Patients were trained for breath hold technique for 3 to      4 days on CT simulator. Seven  patients being non-compliant to  V-DIBH  therefore 24 patients were simulated for breath hold. We made tangential IMRT plans for all the patients on both V-DIBH and free breathing scans for dosimetric comparison. D95% target and organ at risk (OARs) like Dmean of heart, LAD, lung and opposite breast were compared for both plans. Results: A significant reduction of mean cardiac dose from 5.7 ± 1.58 Gy to 3.45 ± 0.68 Gy (p<.05) and cardiac V25Gy from 7.28 ±3.97 % to 1.64 ± 1.35% (p<.05) in V-DIBH cases as compared to FB. Mean dose to the LAD was reduced by 3.9 Gy in DIBH cases (p<.05). Differences between FB and V-DIBH mean lung dose was 2.47 Gy (p=.106, ns) and ipsilateral lung V20Gy was 2.57% (p=.078, ns). Conclusion: This study demonstrates dosimetric benefits of V-DIBH over FB in reducing dose to heart, LAD and ipsilateral lung without compromising the target volume coverage. We should opt for V-DIBH over FB for left sided breast cancer cases